The research of the transport infrastructure development in Ternopil - Popovych Pavlo; Rozum Ruslan; Shevchuk Oksana; Buriak Mykola; Chorna Olga; Zaharchuk Olena; Brych Vasyl; Rudyak Yurii; Falovych Nataliia; Borysiak Olena; Maiak Mykola; Melnychenko Vasyl (MATEC Web of Conferences, 2024)
The article is devoted to the problem of studying the state of transport infrastructure of the city of Ternopil in order to further develop a plan for sustainable urban mobility for territorial community of Ternopil city. To satisfy the existing needs of passengers in high-quality transport service, it is necessary to ensure a sufficient number of buses with large and medium passenger capacities. However, according to the principles of sustainable urban mobility, exploitation of the new “green” electric vehicles should be the priority for the modern transport policy of the community. Currently, the most problematic situation with insufficient parking spaces can be observed in the central part of Ternopil. In particular, the city is experiencing such situation due to the growing level of motorization of residents of Ternopil territorial community and, accordingly, the growing demand for the use of individual transport. To solve the current problem, various sources of financing, such as the city budget, the state budget, investments, loans, funds of individuals and legal entities are attracted. Despite this, the implementation of measures still largely depends on the local budget. Analysis of the allocation and development of fundings showed that there has been a prolonged underfinancing of works related to the transport infrastructure of Ternopil. An analysis of the actual indicators of the development of financial resources that have been allocated from the local budget to improve the state of SN for 2020 showed that they did not reach the planned values by 36.4%. Also, in 2020, according to the local budget, it was planned to finance the Program for the development of bicycle infrastructure of the city. The amount of financing was meant to be 2000.0 thousand UAH. However, in fact, no investments were actually made.